Correlation among the level of Education and Economic Development-A myth and reality - Saikia, Dr. Biren (International Journal of Advanced Science and Technology, 2020)
Economic development is a powerful change in which real per capita income has increased over a long period of time. A person’s per capita income increases when people acquire or incorporate knowledge or basic educational elements are fundamentally strong and sustainable. As we know, education is the most important tool for changing the economic conditions of rural society. It is also crucial for all aspects of social and economic development. Economic development is a measure of human well-being in a society and education is an important part of a region’s development. Not only does it help farmers plan and manage, make rational decisions, keep records, calculate costs and revenues, but also provide knowledge to adopt better farming methods, understand processing methods and conservation procedures, learn about programs, the objectives and policies of the government, knowing the well-being of the family, health, nutrition and the domestic economy, etc. Therefore, this document has attempted to see the relationship between education and economic development and its problems and suggestions regarding economic development.